TINDAK UJAR ILOKUSI DALAM NOVEL THE THREE MUSKETEERS KARYA ALEXANDRE DUMAS - Ambeua, Seyla Dea Justisia; Jansen, Frieda Th.; Pamantung, Rina P. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTARCT          The study entitled Illocutionary Acts in the Novel The Three Musketeers by Alexandre Dumas. In doing this research the writer used Searle’s theory (1970). According to Searle, illocutionary is a part of speech act and speech act is the center of Pragmatics. Illocutionary act menas uttering a certain sentence with a certain sense and references. Serale devided ilocutionary act into five categories, namely assertives, directives, commissive, ekspressive and declarative. The purpose of this research is to identify, clasify and analyze the function of illocutionary act in the novel The Three Musketeers by Alexandre Dumas. The collected data have been indentified to the utterancess with contain illocutionary act that are used by the characters in the novel and analyze descriptively based on Searle’s theory. The result shows that there are five kinds of illocutionary act in the novel. Those are asserives, directives, commissives, ekpressives and declaratives. The function of illocutionary act in the novel are suggesting, stating, greeting, aplogizing, thanking and declaration. It is expected that the study can help the readers especially the student in learning pragmatics specifically illocutionary act in the novel The Three Musketeers by Alexandre Dumas.Keywords: Illocutionary Act, Pragmatics, Novel The Three Musketeers